2016
DOI: 10.1097/txd.0000000000000629
|View full text |Cite
|
Sign up to set email alerts
|

Increased Telomere Attrition After Renal Transplantation—Impact of Antimetabolite Therapy

Abstract: BackgroundThe uremic milieu exposes chronic kidney disease (CKD) patients to premature ageing processes. The impact of renal replacement therapy (dialysis and renal transplantation [RTx]) or immunosuppressive treatment regimens on ageing biomarkers has scarcely been studied.MethodsIn this study telomere length in whole blood cells was measured in 49 dialysis patients and 47 RTx patients close to therapy initiation and again after 12 months. Forty-three non-CKD patients were included as controls.ResultsNon-CKD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 56 publications
4
14
0
Order By: Relevance
“…We found further a significant positive correlation between increased gene expression of TRF2 and RPA1 and hsCRP, which supports the previous findings that deteriorating graft function and chronic inflammation may affect telomere stability in the KTx population. 18,21 To the best of our knowledge, this is the first study reporting the impact of pediatric KTx on telomere length and telomere-binding proteins at adult age.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…We found further a significant positive correlation between increased gene expression of TRF2 and RPA1 and hsCRP, which supports the previous findings that deteriorating graft function and chronic inflammation may affect telomere stability in the KTx population. 18,21 To the best of our knowledge, this is the first study reporting the impact of pediatric KTx on telomere length and telomere-binding proteins at adult age.…”
Section: Discussionmentioning
confidence: 92%
“…End-stage kidney disease and immunosuppressive medication have been shown to shorten telomere length. [16][17][18]20 In the present study, we evaluated the telomere length and expression of genes encoding telomere-binding proteins in a cohort of young men with a history of long-lasting exposure to immunosuppressive medication due to KTx during childhood. The results were compared with those of healthy controls and with another control group comprising survivors of childhood NBL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…118 Recent evidence has indicated a link between immunosuppressive therapy, aging and homocysteine biochemistry in renal transplant recipients. 119 Longitudinal analyses of aging in CKD have indicated that these patients displayed significantly advanced biological age. 98 Notably, homocysteine is critical for DNA methylation nucleotide biosynthesis and maintenance of genomic integrity.…”
Section: Epigenetics and Inflammagingmentioning
confidence: 99%
“…120,121 Impact on the cellular methylome in these circumstances seems intuitive, but requires further investigation to determine if any changes in its status either drive the accelerated aging, or are a consequence of it, or of any clinical interventions. 119 At a cellular level, recent evidence suggests an important role for the SASP in the pathogenesis of inflammaging. Senescent cells are pro-inflammatory 122 .…”
Section: Epigenetics and Inflammagingmentioning
confidence: 99%